2010
DOI: 10.1194/jlr.m002204
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal absorption of dietary maize glucosylceramide in lymphatic duct cannulated rats

Abstract: mammalian sphingolipids is sphingosine ( trans -4-sphingenine, d18:1 4t ). Smaller amounts of other sphingoid bases, such as sphinganine (dihydrosphingosine, d18:0) and phytosphingosine (4-hydroxysphinganine, t18:0), are encountered frequently. In higher plants, the structures of sphingoid bases are more complicated than in mammals, because they can be desaturated at the C8-position by a ⌬ 8-sphingolipid desaturase, yielding cis -and trans -isomers of ⌬ 8-unsaturated sphingoid bases (d18:2 4t,8c(t) ) ( 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
104
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(112 citation statements)
references
References 47 publications
6
104
2
Order By: Relevance
“…Glucosylceramides were prepared from maize by using a silica gel column after lipid extraction and saponification as described previously (17,18). Trans-4,cis-8-sphingadienine (d18:2 4t,8c ) was prepared from maize glucosylceramide after acid hydrolysis and was purified by using high-performance liquid chromatography (HPLC) as described previously (19).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucosylceramides were prepared from maize by using a silica gel column after lipid extraction and saponification as described previously (17,18). Trans-4,cis-8-sphingadienine (d18:2 4t,8c ) was prepared from maize glucosylceramide after acid hydrolysis and was purified by using high-performance liquid chromatography (HPLC) as described previously (19).…”
Section: Methodsmentioning
confidence: 99%
“…We previously demon-strated that the digestibility of glucosylceramide derived from higher plants is similar to that of glucosylceramide derived from mammals, but the metabolic fate of plantderived sphingoid bases within enterocytes differs from that of sphingosine (17). A lipid absorption assay of lymph obtained from the thoracic duct revealed that the absorption rate of 4,8-sphingadienine from dietary plant-derived glucosylceramide in the intestine is lower than that of sphingosine (18). According to the results of a study of cultured cells, sphingoid bases, except for sphingosine, appear to be transported out of cells across the apical membranes of enterocytes by P-glycoprotein after absorption (19).…”
mentioning
confidence: 99%
“…This indicates that a small amount of topical GluCer is enough to inhibit skin photoaging. In our previous study, maize GluCer was only slightly absorbed by the intestine in rats 8,9 . In light of this fi nding, we investigated whether the topical GluCer was absorbed into the skin of the mice in this study.…”
Section: Resultsmentioning
confidence: 99%
“…However, we have previously reported that dietary maize GluCer was only slightly absorbed by the rat intestine 8,9 . It appears that plant sphingolipids are barely re-utilized in skin, and the mechanism underlying the improving effect of dietary plant sphingolipids on skin barrier functions is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, dietary GlcCer and SM improve clinical symptoms and epidermal barrier function of AD, 30,31 implying the direct reutilization of dietary GlcCer and SM for Cer generation in epidermis. However, with extremely low absorption of dietary GlcCer in the intestine, 32 the beneficial effects of dietary GlcCer and SM in AD skin is explained rather by the selective upregulation of Cer synthase 3 and 4 mRNAs. 30 On the other hand, ingested LE extracts decrease the serum levels of insulin and leptin, which indirectly mediate a decreased expression of lipogenic genes in the liver.…”
mentioning
confidence: 99%